Digital Marketing as an Investment in Micro, Small and Medium Enterprises (MSME) of Fruit Plant Nurseries - Kurnia, Aang (Economic Education and Entrepreneurship Journal, 2024)
Digital marketing through social media can be an effective marketing strategy, because it can reachconsumers widely. Digital marketing is also a form of investment to increase sales results and increase the value of business assets. This study aims to determine the type of digital marketing used in Micro, Small and Medium Enterprises (MSME)  Naura Flower fruit plant nursery as a form of investment that can make these MSME more advanced and developed. Data collection techniques in this study used triangulation by combining observation, interview and documentation techniques. This research was conducted at the Naura Flower fruit plant nursery Micro, Small and Medium Enterprises (MSME). Based on the results of the study that Micro, Small and Medium Enterprises (MSME) of Naura Flower fruit plant nursery have used Social Media Marketing (SMM) through social media WhatsApp and Facebook as a form of digital marketing investment. Naura Flower only uses one type of digital marketing, namely Social Media Marketing (SMM). Naura Flower also states that digital marketing is one part of a long-term investment for the progress and sustainability of Micro, Small and Medium Enterprises (MSME) in increasing sales results and increasing the value of business assets. This research is expected to provide insight for Micro, Small and Medium Enterprises (MSME) to be able to utilize and use digital marketing as a strategy.Keywords: Digital Marketing, Investment, Micro Small and Medium Enterprises (MSME)DOI: http://dx.doi.org/10.23960/E3J/v7i1.88-93